The Efficacy of Chaihu-Guizhi-Ganjiang Decoction on Chronic Non-Atrophic Gastritis with Gallbladder Heat and Spleen Cold Syndrome and Its Metabolomic Analysis: An Observational Controlled Before-After Clinical Trial [Letter] - Zhu Y; Geng S; Zhu F (Dove Medical Press, 2024)
Ying Zhu, Shiyu Geng, Feiye Zhu School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Feiye Zhu, School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China, Email zhufeiye@163.com